Edukasi Sanitasi Dan Kebersihan Lingkungan Dengan Media Permainan Ular Tangga Di SMA Mathla’ul Anwar Menes Kabupaten Pandeglang - Siti Nur Ramdaniati; E. Egriana Handayani; Erma Noor Wahyuningsih; Heny Sasmita; Lambang Satria Himmawan; Ucu Wandi Somantri (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Environmental Health efforts are one way of achieving a healthy environmental quality, both physical, chemical, biological and social, enabling every community to the highest level of Health with the media of the snake game staircase. Nearly 80% of diseases in schools are caused by poor sanitation and hygiene conditions. Therefore, there is a need for education aimed at improving the knowledge of students and changing the thinking of students in keeping the sanitation and hygiene of the environment at school. This educational activity was carried out at Mathla’ul Anwar Menes Pandeglang Banten. The methods used in this research are lectures with an educational approach using power point media and a snake game of stairs. To measure the level of knowledge of students in this study using pre-test post-test. This education has an effect on the changes in knowledge, attitudes and actions of students about sanitation and environmental hygiene, as evidenced by respondents' answers.